FUEL SUBSIDY REMOVAL AND GOVERNMENT POLICY ON POVERTY ALLEVIATION IN NIGERIA (2015 – 2023) - IBRAHIM KASIM KESINTON (International Studies Journal)
The study has tried to find out the impact of fuel subsidy on government poverty alleviation policies. Successive governments in Nigeria have announced reduction in the amount of subsidy it is paying on petroleum products persistently. The study used qualitative data in its investigation. The study found out that fuel subsidy removal had both positive and negative impact on the governments’ poverty alleviation policies. The study recommends that government should put adequate measures on ground in order to ensure that fuel subsidy removal do not have adverse effect on its poverty alleviation policies because poverty alleviation policies are essentially tools in addressing the impact of fuel subsidy removal.